PENGARUH MUATAN ETIKA DALAM PENGAJARAN AKUNTANSI KEUANGAN, KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL TERHADAP SIKAP ETIS MAHASISWA AKUNTANSI (Studi pada mahasiswa Universitas Islam Malang dan Universitas Gajayana Malang) - Hikmatul Amaliya; Moh. Amin; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis research was conducted to analyze the Effect of Ethical Content in the Teaching of Financial Accounting for Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence on the Ethical Attitudes of Accounting Students. The population sampled in this study is the Faculty of Economics and Business, Islamic University of Malang and University of Gajayana Malang with the criteria of respondents, namely students who have taken financial accounting courses in 2016 and 2017. The analytical methods used are Multiple Linear Regression with software SPSS 22 For windows. Based on the sampling method obtained 86 respondents. Based on the results of the hypothesis test the results obtained that the test results simultaneously show a value of Fcount of 5.210 with a significant F of 0.000 (0,000 <0.05) so that it can be concluded that simultaneously the data of Accounting Ethics, Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence influence attitudes ethical accounting students. Emotional intelligence does not affect the ethical attitude of accounting students. The results of the test of spiritual intelligence indicate that H1 is accepted, so it can be concluded that partially the spiritual intelligence variable influences the ethical attitude of accounting students.Keywords : Content of Ethics in Teaching Financial Accounting Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence, Ethical Attitude of Accounting Students.